The Association of Self-Reported Iron and Vitamin D Levels on Sleep Quality and Pain Perception in a Subset of Saudi Population - Al-Khudhairy MW (Dove Medical Press, 2021)
May Wathiq Al-Khudhairy,1 AlAnoud AlOtaibi,2 Latifa AbdulRahman,2 Maha Al-Garni,2 Rahaf Yaslam,2 Rana Fatani2 1Oral Biology, Department of Oral Maxillofacial Surgery and Diagnostic Sciences, College of Dentistry, Riyadh Elm University, Riyadh, Saudi Arabia; 2Riyadh Elm University, Riyadh, Saudi ArabiaCorrespondence: May Wathiq Al-Khudhairy Tel +966 503476722Email may_al-khudhairy@post.harvard.edu; may.alkhudhairy@Riyadh.edu.saBackground and Aims: There has been a rising concern regarding the relationship of iron levels, vitamin D, and consumption of multivitamins on pain perception and sleep quality. The purpose of this study is to shed light on these connections in hopes of enhancing quality of sleep.Methods: A cross-sectional analysis was used, and data collection was based on close-ended online questionnaire created on Survey Monkey. The survey included an operator designed questionnaire, questions from both the Brief Pain Inventory and Sleep Quality questionnaires. The targeted population was participants who were medically fit, non-pregnant Saudi citizens aged between 25 and 55 years.Results: Prior to the COVID-19 crisis, data were collected during the months of February and March 2020, with a grand total of 3127 participants, out of which 2774 responses were included. The outcome of the research revealed that diminished levels of vitamin D, and iron had a negative impact on sleep quality. In turn, poor sleep quality had a significant pain response.Conclusion: This study reveals the detrimental role of vitamins on sleep, and their concurrent domino effect on pain.Keywords: daylight, iron, pain, sleep quality, vitamin D